﻿Transient receptor potential Ankyrin 1: structure, function and ligands - Natalia V. Pyatigorskaya; Olga V. Filippova; Natalia S. Nikolenko; Aleksey D. Kravchenko (Belgorod National Research University, 2022)
Introduction: Transient receptor potential ankyrin 1 (TRPA1) is a protein expressed in many living organisms. During the study of TRPA1, its unique biological role as a universal and polymodal sensor of various altering agents was found. The aim of this study is to search and generalize information about structural features and molecular determinants, mechanisms of activation, action and modulation of TRPA1 as a universal pain and inflammation sensor, as well as the nature of activators and antagonists of this target and their therapeutic potential. Materials and methods: This article presents an overview of the results of scientific research of TRPA1, its modulators, as well as an overview of their pharmacological potential over the period from the discovery of these channels to the present, with an emphasis on the last decade. Results and discussion: The main collected data on expression, structural features and molecular determinants, mechanisms of activation and action of TRPA1 indicate its role as a universal and labile element of the primary response of the body to adverse exogenous and endogenous factors. Regardless of the nature of the stimulus, hyperstimulation of TRPA1 channels can lead to such phenomena as pain, inflammation, itching, edema and other manifestations of alteration, and therefore TRPA1 blockade can be used in the treatment of various diseases accompanied by these pathological conditions. Currently, TRPA1 antagonists are being actively searched for and studied, as evidenced by a high patent activity over the past 14 years; however, the molecular mechanisms of action and pharmacological properties of TRPA1 blockers remain understudied. Conclusion: Acquire of new information about TRPA1 will help in the development of its modulators, which can become promising analgesics, anti-inflammatory drugs, bronchodilators, and agents for the treatment of cardiovascular diseases of new generations.